2022
DOI: 10.1002/chir.23436
|View full text |Cite
|
Sign up to set email alerts
|

Chiral NMR analysis reveals the environmental dependence of areolal scalemization in Piptothrix areolare

Abstract: The occurrence of racemic and enantiomerically enriched (scalemic) mixtures of secondary metabolites in their natural sources is a rare phenomenon. The unprecedent case of enantiomeric variations from levorotatory to dextrorotatory, and back to levorotatory, passing through an almost racemic mixture, was recently documented for areolal, the major epoxythymol of Piptothrix areolare. In an attempt to shed some light to understand the reasons for such an unusual behavior, herein, we evaluated this phenomenon by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Prolonged exposure to more suitable environments may lead to long-term adaptations in these plants, potentially resulting in morphological and physiological alterations in their nutrient organs (Velten & Richter 1993). Upon transplantation into natural habitats, abrupt environmental changes threaten plants' normal survival, necessitating excessive energy expenditure for acclimation (G omez-Hurtado et al 2022). Yang et al (2011) and Shi et al (2020) also demonstrated that terrestrial plants subjected to extended laboratory conditions experience environmental stresses upon field transplantation, leading to a decline in plant dry matter content by approximately 30-45% compared with that of laboratory-grown counterparts.…”
Section: Physiological Response Of Seagrasses To Different Plant Cult...mentioning
confidence: 99%
“…Prolonged exposure to more suitable environments may lead to long-term adaptations in these plants, potentially resulting in morphological and physiological alterations in their nutrient organs (Velten & Richter 1993). Upon transplantation into natural habitats, abrupt environmental changes threaten plants' normal survival, necessitating excessive energy expenditure for acclimation (G omez-Hurtado et al 2022). Yang et al (2011) and Shi et al (2020) also demonstrated that terrestrial plants subjected to extended laboratory conditions experience environmental stresses upon field transplantation, leading to a decline in plant dry matter content by approximately 30-45% compared with that of laboratory-grown counterparts.…”
Section: Physiological Response Of Seagrasses To Different Plant Cult...mentioning
confidence: 99%